2011
DOI: 10.1074/jbc.m110.202366
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Pore Opening of Acid-sensing Ion Channel 1A

Abstract: Acid-sensing ion channels (ASICs) are trimeric cation channels that undergo activation and desensitization in response to extracellular acidification. The underlying mechanism coupling proton binding in the extracellular region to pore gating is unknown. Here we probed the reactivity toward methanethiosulfonate (MTS) reagents of channels with cysteine-substituted residues in the outer vestibule of the pore of ASIC1a. We found that positively-charged MTS reagents trigger pore opening of G428C. Scanning mutagene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…1 (21,22). We previously showed that mASIC1a resides in a responsive closed state at pH values above 7.4, but it desensitizes when the extracellular pH decreases below 7.2 (19). Thus, we probed the reactivity toward MTSET of channels bearing individual Cys mutations at selected sites in the acidic cluster at pH 7.0, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…1 (21,22). We previously showed that mASIC1a resides in a responsive closed state at pH values above 7.4, but it desensitizes when the extracellular pH decreases below 7.2 (19). Thus, we probed the reactivity toward MTSET of channels bearing individual Cys mutations at selected sites in the acidic cluster at pH 7.0, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…These channels desensitize over a narrow range of pH. At pH values above 7.4, ASIC1a exists in the closed state, whereas at pH values below 7.2, it resides in the desensitized state (21,24). To define structural changes associated with pore opening, we explored the reactivity of MTSET with channels bearing single Cys mutations in the tract 426 -438 at pH 6.5, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…To contribute to ion selectivity, residues in the (G/S)XS tract must undergo a considerable movement toward the center of pore during opening. We have proposed that a rotation of the TM2 segments could widen the closed gate and move toward the center of the pore residues that contribute to ion selectivity in the distal region of the TM2 segments (24).…”
Section: Discussionmentioning
confidence: 99%
“…The half-time of hydrolysis of MTSET in the recording solution of pH 7.0 is 130 min (36). Therefore, solutions buffered at pH 7.0 containing MTS reagents were used within 30 min of preparation.…”
Section: Methodsmentioning
confidence: 99%